STUDY OF AREAL REGULARITIES OF CHANGES IN CAPACITIVE PROPERTIES OF RESERVOIRS ACCORDING TO LOGGING DATE - BEZRODNA, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The possibilities of the determination of areal regularities of the transformation of empty space of composite terrigenous reservoirs are under study on the data of geophysical investigation of the bore holes. Concentration emptiness calculated of formats are defined, roc-collectors beds, the types of reservoirs evaluated. On the maps and three-dimensional images of selected areas of advanced collectors for each of the productive horizons.